Mendelian randomization of plasma lipids and aortic valve stenosis: the importance of outlier variants and population stratification - Nazarzadeh, M; Rahimi, K (Oxford University Press, 2020)
This commentary refers to ‘Plasma lipids and risk of aortic valve stenosis: a Mendelian randomization study’, by M. Nazarzadeh et al., doi:10.1093/eurheartj/ehaa070.